2014
DOI: 10.1136/bcr-2014-206003
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid volvulus in an adolescent girl: staged management with emergency colonoscopic reduction and decompression followed by elective sigmoid colectomy

Abstract: A case of acute sigmoid volvulus in a 14-year-old adolescent girl presenting with acute low large bowel obstruction with a background of chronic constipation has been presented. Abdominal radiograph and CT scan helped in diagnosis. She underwent emergency colonoscopic detorsion and decompression uneventfully. Lower gastrointestinal contrast study showed very redundant sigmoid colonic loop without any transition zone and she subsequently underwent elective sigmoid colectomy with good outcome. The sigmoid volvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Although our patient was adoloscent, the average age of child reported is eight years with male preponderance (male/female ratio 3.5:1) [1]. Patel RV et al recently reported adolescent girl with sigmoid volvulus presented with complete large bowel obstruction [10]. The incidence of volvulus in adults is higher in Africa, the Middle East, Asia, and Russia which reported as “Volvulus Belt”.…”
Section: Discussionmentioning
confidence: 89%
“…Although our patient was adoloscent, the average age of child reported is eight years with male preponderance (male/female ratio 3.5:1) [1]. Patel RV et al recently reported adolescent girl with sigmoid volvulus presented with complete large bowel obstruction [10]. The incidence of volvulus in adults is higher in Africa, the Middle East, Asia, and Russia which reported as “Volvulus Belt”.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the present anatomic variation constitutes a major risk factor of sigmoid volvulus [ [1] , [2] , [3] , [6] , [7] , [11] , [15] ]. Indeed, the redundant loop of sigmoid colon may rotate around its narrow, extended mesocolon and provoke lymphovascular congestion and obstruction, followed by distension of the affected loop of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Sigmoid volvulus is the third most common cause of large intestinal obstruction in adults; however, it is very rare in children 3,[5][6][7][8][9][10][11] . There are few cases of sigmoid volvulus reported in children in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al in his review of literature encountered 23 cases of sigmoid volvulus in both children and adults, which were the result of Hirschsprung's disease 6 . Rectal biopsy should be taken before the definite resection procedure whenever Hirschsprung's is suspected clinically or radiographically 8 . The acute management of sigmoid volvulus in non perforated colon involves an initial non-surgical detorsion followed by an elective sigmoidectomy, while surgery is the first approach for sigmoid volvulus with perforation 7 .…”
Section: Discussionmentioning
confidence: 99%